Role of E-Learning in Promoting Distance Learning at Public Schools in Hawalli, Kuwait - Hussain Muhammad Yusuf Jarkhi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Aims: This study aims to identify the role of e-learning in promoting distance learning at public schools in the Hawalli region from teachers' point of view. Methods: A questionnaire consisting of (20) items was developed and was randomly distributed to (50) public school teachers in Hawalli. The questionnaire's validity and reliability were confirmed by a committee of specialized referees. Results: This study came out with several results, the most important of which is that the role of e-learning in promoting distance learning at public schools in the Hawalli region from the teachers' point of view was vital. In addition, it was found that there are no statistically significant differences at the level (α = 0.05) in the average responses of the study sample members to the role of e-learning in promoting distance learning at public schools in the Hawalli region, due to gender, educational qualification, or years of experience. Conclusion: The study recommends conducting e-learning according to a virtual classroom system in order to enhance distance learning. It also recommends the need to build appropriate online tests to the educational material as well as the levels of students in order to assess students in distance education.